The Influence of The Leadership Style of The Head of Madrasah, Teacher Capabilities on Teacher Performance in Tsanawiyah Madrasah Hikmatul Amanah Mojokerto - Idrus, Ali; Tukiyo, Tukiyo; Rosmika, Enita; Sya'roni, Muhammad; Hidayat, M. (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Every educational institution has a leader who has different abilities and leadership styles in improving the performance of their employees. In addition to the leadership style, performance is also influenced by the capabilities of each employee. This study aims to determine whether the principal's leadership style (X1) and teacher capability (X2) on teacher performance (Y) either partially or simultaneously, and which independent variables (X1 and X2) have a more significant influence on teacher performance. This research is a quantitative study that aims to test hypotheses between variables. The data used are primary data obtained directly from the respondents, as many as 48 people through filling out a questionnaire. The data analysis technique uses multiple linear regression, which is processed using SPSS. At the same time, all instruments in this study have been tested for validity and reliability, where all instruments have been declared valid because of the value T count > T table. In contrast, it has been declared reliable because it is greater than the Cronbach alpha value of 0.60 processed. They were using SPSS. The T-test results of leadership style obtained a sig value of 0.002 and a teacher's capability value of 0.000. These results indicate that the variables of leadership style and teacher capability significantly influence teacher performance. In contrast, the teacher capability variable has a more significant influence on teacher performance.